Nivel de Satisfacción del Usuario de las Carreteras: Método Delphi - Silva, Sergio Antonio; Galindo Montiel, Yolanda; Mendoza Puga, Luis Enrique (Acta Universitaria, 2002)
Strategies for the maintenance of roads are typically determined based on technical criteria, that use indicators which were obtained using sophisticated equipment and interpreted by the expert on roads (e. g. international roughness index, pavement deformation, and physical condition evaluation). However, road user’s opinion is not considered. This paper analyses the pertinence of considering the road user’s opinion to obtain parameters that could be used as an additional criteria when evaluating the quality of the offered service and defining maintenance strategies by road operator organisms. Obtained parameters are validated and using the Delphi technique they were weighted and assembled into a unique value termed Road User Service Level Indicator — Indicadordel Nivel de Servicio del Usuario de las Carreteras (INSUC).